2018
DOI: 10.1103/physrevb.97.035203
|View full text |Cite
|
Sign up to set email alerts
|

Analog Sauter-Schwinger effect in semiconductors for spacetime-dependent fields

Abstract: The Sauter-Schwinger effect predicts the creation of electron-positron pairs out of the quantum vacuum via tunneling induced by a strong electric field. Unfortunately, as the required field strength is extremely large, this fundamental prediction of quantum field theory has not been verified experimentally yet. Here, we study under which conditions and approximations the interband tunneling in suitable semiconductors could be effectively governed by the same (Dirac) Hamiltonian, especially for electric fields … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…To obtain the spectrum we now only have the Fourier integral left, and to perform it we need to specify the shape of the weak field. We begin with the Sauter pulse (14). We perform the Fourier integral with the saddle-point method.…”
Section: Sauter Pulsementioning
confidence: 99%
See 2 more Smart Citations
“…To obtain the spectrum we now only have the Fourier integral left, and to perform it we need to specify the shape of the weak field. We begin with the Sauter pulse (14). We perform the Fourier integral with the saddle-point method.…”
Section: Sauter Pulsementioning
confidence: 99%
“…Many aspects in Schwinger pair production have close analogies in tunneling in semiconductors [14]. In particular, dynamically assisted Schwinger pair production is analogous to the Franz-Keldysh effect [14][15][16][17], where semiconductor tunneling in an electric field is assisted by higher-frequency photons. The Franz-Keldysh effect in QED was very recently studied in [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Dirac picture of particle-antiparticle vacuum and the concept of optical lattice band theory is the foundation of our approach. In this framework, we readily measured pair creation and demonstrated that this high-field phenomenon is well-characterized by Landau-Zener tunneling [20,21] as was discussed in [12,[17][18][19].…”
Section: Introductionmentioning
confidence: 88%
“…Electric fields on this scale are not experimentally accessible; even the largest laboratory fields produced by ultrashort laser pulses [6] fall short, making direct observation of pair creation out of reach of current experiments. Subsequently, analog experiments have been proposed that simulate high-field effects with laboratory accessible energy scales in cold atoms [7][8][9][10], graphene [11][12][13][14][15][16], and other condensed matter systems [12,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%